Consumption Downgrade and Low-End Disruptive Innovation: Driving Mechanisms, Practical Paths and Impact Effects from a Global Perspective - Chen, Ruoxin (Exploring Science Academic Conference Series, 2026)
Driven by macroeconomic fluctuations, changes in household income expectations, and shifts in consumption values, “consumption downgrading” has become a prominent feature of China’s consumer market, forcing enterprises to pursue innovation. Disruptive innovation offers a viable path for enterprises to achieve breakthroughs; however, existing research has not systematically explored the intrinsic correlation between the two. This study reviews relevant literature, clarifies their relationship and mechanism of action, proposes three pathways of disruptive innovation, identifies the dual impact of consumption downgrading thereon, and ultimately concludes that the two form a complex interactive mechanism through mediating variables such as perceived value. This research fills a gap in the existing literature and provides practical guidance.